Introgression of genes associated with yield enhancement and resistance against bacterial leaf blight and blast diseases into an elite rice variety, Jaya - G. D. Dileep Kumar; R. Abdul Fiyaz; Kasarla Chaithanya; Shivani Darmagaru; K. P. Viswanatha; Payal Patwari; Sathwik Bupalli; V. P. Chimote; K. S. Raghuwanshi; M. B. V. N. Kousik; V. S. Rapaka Percy; M. Bharath; et al. (The Plant Genome)
Abstract Developing rice (Oryza sativa L.) cultivars with resistance to bacterial leaf blight (BLB) and blast is crucial for ensuring food security, as these diseases can cause significant yield losses. Additionally, enhancing yield potential in these resistant cultivars can maximize productivity and meet the growing demand for rice; therefore, introgression of bacterial leaf blight and blast resistance genes along with yield improvement genes is the most felicitous strategy for a panoramic genetic enhancement. Jaya is a most popular, stable mega rice variety, notified and cultivated in 19 states across India, and is susceptible to bacterial leaf blight and blast diseases and has an average yielding ability (4.5 t/ha). In the current investigation, efforts have been made to transfer Xa21 for BLB resistance, Pi54 for blast resistance, and Gn1a for yield improvement. A total of 20 BC2F2 introgression lines with targeted BLB, blast, and yield genes were identified. Based on preliminary yield trials in BC2F3 generation, two best lines (BC2F2‐2‐27‐2 and BC2F2‐2‐27‐4) and which showed higher phenotypic disease resistance along with superior yield performance were selected for multi‐location testing along with recurrent parent. Both the lines performed superior with respect to disease resistance and grain yield, along with acceptable grain quality which can be comparable to the recurrent parent Jaya.